Análise dos lipídios séricos de pacientes obesos mórbidos submetidos ao bypass gástrico - Lubianca, Luiza Marsiaj (2015)
Introduction: The aim of this study was to evaluate the correlation between improvement in dyslipidemia and changes in body fat percentage. Material and Method: We conducted an observational, retrospective cohort study of patients subjected to gastric bypass. We selected patients who underwent bioimpedance analysis before surgery and at 3, 6 and 12 months postoperatively. Patients underwent laboratory tests and anthropometric measurements at the same time. Results: We studied 228 patients with a mean age of 37.4 ± 11.7 years. Most patients were female (76.3%). Initially, 143 patients (66.2%) showed criteria for dyslipidemia, and 6 months after surgery, this number fell to 83 patients (50.6%) and continued falling over time to only 45 patients (28.5%) 12 months after surgery. In relating different variables with the decrease in percent body fat at 12 months, a significant association was seen with weight loss (r=0.258; p=0.009), BMI (r=0.272; p=0.005) and waist circumference (r=0.357, p <0.001). However, the only biochemical parameter showing a significant association was HDL-C level (r=-0.267; p=0.009). Patients with the greatest decrease in body fat percentage were those with the largest decrease in weight, BMI and waist circumference and highest increase in HDL-C level. Conclusion: This study demonstrated the association of decrease in percent body fat with increase in HDL-C, regardless of sex and age. The same association was also observed when using the parameters BMI, weight loss and waist circumference.